2022
DOI: 10.1186/s12870-022-03711-9
|View full text |Cite
|
Sign up to set email alerts
|

Linkage mapping combined with GWAS revealed the genetic structural relationship and candidate genes of maize flowering time-related traits

Abstract: Background Flowering time is an important agronomic trait of crops and significantly affects plant adaptation and seed production. Flowering time varies greatly among maize (Zea mays) inbred lines, but the genetic basis of this variation is not well understood. Here, we report the comprehensive genetic architecture of six flowering time-related traits using a recombinant inbred line (RIL) population obtained from a cross between two maize genotypes, B73 and Abe2, and combined with genome-wide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Therefore, maize flowering time is an important characteristic that determines local environmental adaptation and is easily affected by the local environment. Similar to the findings of a previous study (Shi et al, 2022), the interaction effect of genotype and the environment on maize flowering time-related traits was significant in this study. Revealing the potential genetic basis of flowering time will aid in the selection of stable varieties in different local environments and will improve maize yields.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, maize flowering time is an important characteristic that determines local environmental adaptation and is easily affected by the local environment. Similar to the findings of a previous study (Shi et al, 2022), the interaction effect of genotype and the environment on maize flowering time-related traits was significant in this study. Revealing the potential genetic basis of flowering time will aid in the selection of stable varieties in different local environments and will improve maize yields.…”
Section: Discussionsupporting
confidence: 91%
“…For example, ZmWRKY14 , which is a regulator of maize leaf number, flowering time and biomass yield, has been identified based on GWAS and linkage analysis ( Li et al., 2021 ). By using the same strategy, seventeen candidate genes significantly associated with maize flowering time and leaf number have been found ( Shi et al., 2022 ). In this study, 25 important candidate genes were found by integrating the results of GWASs, QTL mapping, and transcriptome analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, 9 SNPs (82%) associated with ASI were found on chromosomes 1, 3, and 4; for FF trait, 70% (7/10) of SNPs were found on chromosomes 2, 7, and 8; and for FM trait, 4 SNPs (44%) were distributed on chromosomes 1 and 7 ( Supplementary Table S3 ). Previous studies have also identified significant SNPs associated with flowering traits in maize on similar chromosomes ( Li et al., 2016 ; Liu et al., 2019 ; Maldonado et al., 2019 ; Shi et al., 2022 ), suggesting that these regions may contain genes that play a critical role in controlling flowering time variation in maize. The phenotypic variation explained by significant SNPs in this study ranged from 6.7 to 9.6% and was evenly distributed among traits, indicating that many significant SNPs of small effects contribute to genetic variation in flowering time in maize ( Maldonado et al., 2019 ).…”
Section: Discussionmentioning
confidence: 97%